2019
DOI: 10.1186/s41687-019-0094-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Content validity and psychometric evaluation of Functional Assessment of Chronic Illness Therapy-Fatigue in patients with psoriatic arthritis

Abstract: BackgroundTo evaluate the measurement properties (e.g. content validity, reliability and ability to detect change) of the Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue scale in patients with active psoriatic arthritis (PsA).MethodsOne-on-one semi-structured qualitative interviews with adult patients with active PsA evaluated the content validity of FACIT-Fatigue. Quantitative measurement properties were evaluated using data from phase III tofacitinib randomized controlled trials (RCTs) in Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…One concern about utilization of a one-time questionnaire in guiding treatment decisions is that it might not accurately reflect the patient's normal condition. Psychometric assessment has demonstrated that the FACIT fatigue scale is stable overtime with excellent test-retest reliability (12,14). Moreover, even within our dataset, FACIT scores remained relatively stable for patients across the baseline pretreatment visits as well as into the first few treatment visits.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…One concern about utilization of a one-time questionnaire in guiding treatment decisions is that it might not accurately reflect the patient's normal condition. Psychometric assessment has demonstrated that the FACIT fatigue scale is stable overtime with excellent test-retest reliability (12,14). Moreover, even within our dataset, FACIT scores remained relatively stable for patients across the baseline pretreatment visits as well as into the first few treatment visits.…”
Section: Discussionmentioning
confidence: 51%
“…The Functional Assessment of Chronic Illness Therapy Fatigue (FACIT-F) is a 13 point patient reported outcome questionnaire designed to assess a patient's fatigue and its impact on daily functioning. FACIT-F has been widely used in the literature for decades, and has been well validated in a variety of neoplastic and nonneoplastic diseases (12)(13)(14). A recent study on high-grade glioma patients found that FACIT-F scores were strong independent predictors of survival, with patients who were severely fatigued (FACIT-F < 35) had statistically worse survival outcomes compared to the less fatigued group (FACIT-F > 35) (15).…”
Section: Introductionmentioning
confidence: 99%
“…The SPIRIT trials included the fatigue NRS as the sole measurement of fatigue because at the time the trials were designed, there was no single measure favoured to assess symptoms of fatigue in PsA patients and the fatigue NRS was considered a clinically relevant (useful and easy to apply in a clinical practice setting) and acceptable endpoint. Since that time, additional publications describing the psychometric properties of the FACIT-fatigue in PsA patients are now available and the evolution of the PsAID, which includes a fatigue NRS item, has now been provisionally endorsed by Outcome Measures in Rheumatology (OMERACT) for use in PsA clinical trials, further expanding options for evaluating fatigue in this patient population 43 44…”
Section: Discussionmentioning
confidence: 99%
“…The FACIT–F is a self–reported instrument that assesses tiredness, weakness, and difficulty conducting usual activities due to fatigue over the previous 7 days [ 17 ]. The FACIT–F includes 13 items, and all items are rated on a 5–point scale, with options ranging from “not at all (0)” to “very much (4)”, and a higher score indicating higher levels of fatigue [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The FACIT–F is a self–reported instrument that assesses tiredness, weakness, and difficulty conducting usual activities due to fatigue over the previous 7 days [ 17 ]. The FACIT–F includes 13 items, and all items are rated on a 5–point scale, with options ranging from “not at all (0)” to “very much (4)”, and a higher score indicating higher levels of fatigue [ 17 ]. To date, the FACIT–F is available in more than 70 languages on the FACIT official website ( http://www.facit.org/ ), and it has been widely applied in various cancer populations, such as patients with prostate cancer and colorectal cancer, and shows satisfactorily psychometric properties results [ 18 ].…”
Section: Methodsmentioning
confidence: 99%